Immigrant entrepreneurship: a review and research agenda - Dabić, Marina (2020)
Immigrant entrepreneurship has become a phenomenon of global interest. This paper reviews existing immigrant entrepreneurship literature in order to map out the major streams of research and identify widely used theories, methods, and contexts. To do this, the authors have reviewed 514 articles from academic journals. This paper highlights the need for interdisciplinary approaches that transcend boundaries. The development and adoption of different theoretical frameworks, the use of multi-level methods, and the consideration of unexplored country contexts are among the authors’ recommendations for future research.